2006
DOI: 10.1617/s11527-005-9010-y
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of SFRC using inverse finite element analysis

Abstract: A method of inverse finite element analysis is used to determine the constitutive relationship of SFRC in tension, using primary experimental data. Based on beam bending test results and results from pull-out tests, an attempt is made to explain the physical processes taking place during the cracking stage. Basic models predicting the behaviour of SFRC in tension are proposed.Une méthode de FEA réversible est employée pour déterminer le rapport constitutif de SFRC en tension, en utilisant des données expérimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 12 publications
0
42
0
Order By: Relevance
“…A number of available constitutive models for SFRC have been identified such as those proposed by Figueiras (1999, 2001), Lok and Pei (1996), Lok and Xiao (1999), Rilem Technical Committees (2000 and Tlemat et al (2006). The constitutive relations have been developed to describe the uniaxial tensile stress-strain relationship of SFRC.…”
Section: Tensile Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of available constitutive models for SFRC have been identified such as those proposed by Figueiras (1999, 2001), Lok and Pei (1996), Lok and Xiao (1999), Rilem Technical Committees (2000 and Tlemat et al (2006). The constitutive relations have been developed to describe the uniaxial tensile stress-strain relationship of SFRC.…”
Section: Tensile Behaviourmentioning
confidence: 99%
“…Lok and Xiao, 1999;Rilem Technical Committees, 2000Tlemat et al, 2006) suggests that the compressive behaviour of SFRC can be conveniently assumed to be similar to that of plain concrete. Investigations carried out by Bencardino et al (2008) support this conclusion as the observed results show that the addition of steel fibres does not significantly affect the compressive strength of concrete (with potential improved ultimate strain safely ignored).…”
Section: Compressive Behaviourmentioning
confidence: 99%
“…A number of available constitutive models for SFRC have been identified such as those proposed by RILEM (2000RILEM ( , 2003; Barros (1999Barros ( , 2001; Tlemat et al (2006); Lok and Pei (1998); Lok and Xiao (1999). The constitutive relations have been developed to describe the uniaxial tensile stress-strain relationship of SFRC (in particular the post-cracking response allowing for more ductile characteristics compared to the brittle response of plain concrete).…”
Section: Sfrc Constitutive Modelsmentioning
confidence: 99%
“…Swamy and Al-Ta'an 1981;Mansur et al 1986;Bayasi and Gebman 2002;Cho and Kim 2003;Tlemat et al 2006;Campione and Mangiavillano 2008) have been carried out to study how the addition of steel fibres can improve the performance of conventionally reinforced-concrete structures. The studies have shown that steel fibres enhance the ductility of what is considered).…”
Section: Introductionmentioning
confidence: 99%
“…In the RILEM TC 162-TDF (2002) method, strains corresponding to these stresses were empirically estimated as fixed values. The main shortcoming of the RILEM tensile σ-ε response lies in the accuracy of the procedure used to determine the load at initiation of the crack on a measured load-deflection (P-δ) response, not to mention, the assumptions made for the calculation of the post-cracking strength (Tlemat et al, 2006).…”
Section: Introductionmentioning
confidence: 99%